Meningococcal carriage 7 years after introduction of a serogroup A meningococcal conjugate vaccine in Burkina Faso: results from four cross-sectional carriage surveys. Issue 12 (December 2020) - Mbaeyi, Sarah; Sampo, Emmanuel; Dinanibè, Kambiré; Yaméogo, Issaka; Congo-Ouédraogo, Malika; Tamboura, Mamadou; Sawadogo, Guetawendé; Ouattara, Kalifa; Sanou, Mahamadou; Kiemtoré, Tanga; Dioma, Gerard; Sanon, Barnabé; et al.
Summary: Background: In the first 2 years after a nationwide mass vaccination campaign of 1–29-year-olds with a meningococcal serogroup A conjugate vaccine (MenAfriVac) in Burkina Faso, carriage and disease due to serogroup A Neisseria meningitidis were nearly eliminated. We aimed to assess the long-term effect of MenAfriVac vaccination on meningococcal carriage and herd immunity. Methods: We did four cross-sectional studies of meningococcal carriage in people aged 9 months to 36 years in two districts of Burkina Faso between May 2, 2016, and Nov 6, 2017. Demographic information and oropharyngeal swabs were collected. Meningococcal isolates were characterised using whole-genome sequencing. Findings: Of 14 295 eligible people, 13 758 consented and had specimens collected and laboratory results available, 1035 of whom were meningococcal carriers. Accounting for the complex survey design, prevalence of meningococcal carriage was 7·60% (95% CI 5·67–9·52), including 6·98% (4·86–9·11) non-groupable, 0·48% (0·01–0·95) serogroup W, 0·10% (0·01–0·18) serogroup C, 0·03% (0·00–0·80) serogroup E, and 0% serogroup A. Prevalence ranged from 5·44% (95% CI 4·18–6·69) to 9·14% (6·01–12·27) by district, from 4·67% (2·71–6·64) to 11·17% (6·75–15·59) by round, and from 3·39% (0·00–8·30) to 10·43% (8·08–12·79) by age group. By clonal complex, 822 (88%) of 934 non-groupable isolates were CC192, all 83 (100%) serogroup W isolates were CC11, and nine (69%) of 13 serogroup C isolates were CC10217. Interpretation: Our results show the continued effect of MenAfriVac on serogroup A meningococcal carriage, for at least 7 years, among vaccinated and unvaccinated cohorts. Carriage prevalence of epidemic-prone serogroup C CC10217 and serogroup W CC11 was low. Continued monitoring of N meningitidis carriage will be crucial to further assess the effect of MenAfriVac and inform the vaccination strategy for future multivalent meningococcal vaccines. Funding: Bill & Melinda Gates Foundation and Gavi, the Vaccine Alliance.